2005
DOI: 10.1074/jbc.m507993200
|View full text |Cite
|
Sign up to set email alerts
|

γ-Cleavage Is Dependent on ζ-Cleavage during the Proteolytic Processing of Amyloid Precursor Protein within Its Transmembrane Domain

Abstract: ␤-Amyloid precursor protein apparently undergoes at least three major cleavages, ␥-, ⑀-, and the newly identified -cleavage, within its transmembrane domain to produce secreted ␤-amyloid protein (A␤). However, the roles of ⑀-and -cleavages in the formation of secreted A␤ and the relationship among these three cleavages, namely ⑀-, -, and ␥-cleavages, remain elusive. We investigated these issues by attempting to determine the formation and turnover of the intermediate products generated by these cleavages, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
163
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(172 citation statements)
references
References 27 publications
8
163
0
1
Order By: Relevance
“…Preparation of Subcellular Fractions-Cellular cytosolic and nuclear fractions were prepared as described previously (20). Briefly, HUVECs were harvested in homogenization buffer (10 mM MOPS, pH 7.0, 10 mM KCl) containing protease inhibitors (Complete; Roche Applied Science) and processed in a Dounce homogenizer.…”
Section: Materials-human Umbilical Vein Endothelial Cells (Huvecs)mentioning
confidence: 99%
“…Preparation of Subcellular Fractions-Cellular cytosolic and nuclear fractions were prepared as described previously (20). Briefly, HUVECs were harvested in homogenization buffer (10 mM MOPS, pH 7.0, 10 mM KCl) containing protease inhibitors (Complete; Roche Applied Science) and processed in a Dounce homogenizer.…”
Section: Materials-human Umbilical Vein Endothelial Cells (Huvecs)mentioning
confidence: 99%
“…This was not expected because both A␤ and AICD are derived by ␥-secretase activity (9 -11), and it has been reported that the generation of A␤ and AICD are equimolar, at least under basal conditions (46). A␤ generation appears to initially start at the ⑀-cleavage near the cytoplasmic face that first releases AICD from the membrane tether, before -cleavage, and finally, ␥-secretase cleavages occur (47,48). In this model these processive cleavages can be perturbed while keeping ⑀-cleavage relatively intact.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested at 48 hrs and 72 hrs after transfection, lysed in Western blot lysis buffer, and subjected to SDS-PAGE electrophoresis and Western blotting analysis with Ab1 and Ab3 antibodies. N2a cells were cultured and maintained in DMEM supplemented with 10% fetal bovine serum as described previously [15].…”
Section: Rna Interferencementioning
confidence: 99%